Praying in the Breach: Worshiping through the End of Metaphysics - Witherington, Timothy Derrick (Horizons, 2018)
In recent years, discussion has raged within theologies inspired by Continental philosophy of religion regarding the supposed "overcoming" of ontotheology. In this article, I will consider the theological methodology of Louis-Marie Chauvet, a sacramental theologian whose work has been highly influenced by these discussions. For Chauvet, it is the liturgy that provides human beings with the necessary means, not for overcoming ontotheology, but for learning to live with it in a healthy way. Through the liturgy, we learn to work through ontotheology, and thus to hear the call of Being to appropriation and thankful response. This is, however, quite a bit to ask of our liturgies, and I suggest that the only way that Chauvet's method can function is if it is placed in a framework of dialogue. I adopt this framework from Chauvet and expand upon it, which results in an innovative relecture of Chauvet's theology.